Japanese Media Cultures in Japan and Abroad: Transnational Consumption of Manga, Anime, and Media-Mixes - Hernández-Pérez, Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In the last few decades, Japanese popular culture productions have been consolidated as one of the most influential and profitable global industries. As a creative industry, Japanese Media-Mixes generate multimillion-dollar revenues, being a product of international synergies and the natural appeal of the characters and stories. The transnationalization of investment capital, diversification of themes and (sub)genres, underlying threat in the proliferation of illegal audiences, development of internet streaming technologies, and other new transformations in media-mix-based production models make the study of these products even more relevant today. In this way, manga (Japanese comics), anime (Japanese animation), and video games are not necessarily products designed for the national market. More than ever, it is necessary to reconcile national and transnational positions for the study of this cultural production.The present volume includes contributions aligned to the analysis of Japanese popular culture flow from many perspectives (cultural studies, film, comic studies, sociology, etc.), although we have emphasized the relationships between manga, anime, and international audiences. The selected works include the following topics:• Studies on audiences-national and transnational case studies;• Fandom production and Otaku culture;• Cross-media and transmedia perspectives;• Theoretical perspectives on manga, anime, and media-mixes.